A Case study- Jalaukavacharan-Leech Therapyin management of Vranagranthi (Keloid) - B.Padvi, Dr. Sejal; Kumar Sharma, Dr. Rajesh (Asian Journal of Pharmaceutical Research and Development, 2024)
Keloid is a type of scar that results from the overgrowth of dense fibrous tissue which is usually develops after healing of a skin injury. In other words, it represents an abnormal scar formation. The tissue extends beyond the borders of the original wound and does not usually regress spontaneously. It causes cosmetic deformity, itching, pain, and stress ultimately resulting in compromised quality of life and diminished functional performance. The treatment of Keloid is often difficult because there is an associated high risk of recurrence. Vrana represents a vast part of Shalyatantra and the pathogenesis of Keloid is similar to Vrana granthi which has been explained as a growth of mass at the site of Vrana following dietetic complications or any physical irritation in a Vrana patient. Jalaukavacharana (leech therapy) is a parasurgical type of Raktamokshana and is considered as the most unique and effective method of bloodletting. Leeches are widely used in most disorders ranging from skin disease with evidence of successful results. In the present paper, an effort has been made to case of keloid that have been conducted in Ayurveda as para surgical procedure.